Assessment Of Herbal Crude And Extract Of Labisia Pumila By Chemometrics-Assisted Interpretation Of Ftir. - Mustapa, NurulHaniza; Hamdan, Mohammad Razak; Ismail, Zhari (2005)
Pharmacognosical analysis of medical herbs remains as a challenging issue for analytical chemists, as herbs are a complicated system of mixtures.